2006
DOI: 10.1007/s00122-006-0285-3
|View full text |Cite
|
Sign up to set email alerts
|

EST sequencing and phylogenetic analysis of the model grass Brachypodium distachyon

Abstract: Brachypodium distachyon (Brachypodium) is a temperate grass with the physical and genomic attributes necessary for a model system (small size, rapid generation time, self-fertile, small genome size, diploidy in some accessions). To increase the utility of Brachypodium as a model grass, we sequenced 20,440 expressed sequence tags (ESTs) from five cDNA libraries made from leaves, stems plus leaf sheaths, roots, callus and developing seed heads. The ESTs had an average trimmed length of 650 bp. Blast nucleotide a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
108
0
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(111 citation statements)
references
References 21 publications
1
108
0
2
Order By: Relevance
“…Hasterok et al (2004) used FISH to analyze different accessions of Brachypodium and found the 2n = 20 forms to have small chromosomes more similar to those of B. sylvaticum than to the larger chromosomes found in 2n = 10 accessions of B. distachyon. Moreover, 2n = 30 accessions are reported to have C-values approximately twice as large as those for the 2n = 10 forms (Vogel et al 2006), and their karyotypes seem to represent the addition of the chromosomes of the 2n = 10 and 2n = 20 forms. All this suggests that the 2n = 30 forms are allotetraploids formed by hybridization between 2n = 10 and 2n = 20 forms, followed by chromosome doubling (Hasterok et al 2004).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Hasterok et al (2004) used FISH to analyze different accessions of Brachypodium and found the 2n = 20 forms to have small chromosomes more similar to those of B. sylvaticum than to the larger chromosomes found in 2n = 10 accessions of B. distachyon. Moreover, 2n = 30 accessions are reported to have C-values approximately twice as large as those for the 2n = 10 forms (Vogel et al 2006), and their karyotypes seem to represent the addition of the chromosomes of the 2n = 10 and 2n = 20 forms. All this suggests that the 2n = 30 forms are allotetraploids formed by hybridization between 2n = 10 and 2n = 20 forms, followed by chromosome doubling (Hasterok et al 2004).…”
Section: Discussionmentioning
confidence: 97%
“…distachyon has a rapid generation cycle under optimized conditions (8-12 weeks), does not grow very tall (20-30 cm) at high planting densities, requires few demanding growth resources, shows good environmental adaptation ) and the 2n = 10 forms do not require vernalization (Draper et al 2001;Ozdemir et al 2008;Vogel et al 2006). The species B. distachyon has been used to protect rural soils from erosion, especially in slope areas where water runoff, wind and other agents cause soil loss.…”
Section: Introductionmentioning
confidence: 99%
“…Several phylogenetic studies have indicated that Brachypodium and the Triticeae (wheat and barley) are more closely related to each other than to rice (Vogel et al 2006;Bossolini et al 2007;Huo et al 2007). This close relationship suggests that Brachypodium may serve as a better model for Triticeae crop research.…”
Section: Analysis Of Non-colinear Genesmentioning
confidence: 99%
“…The genus Brachypodium belongs to the Brachypodieae tribe, which is sister group to the four major cool season grass tribes of great economic importance-Triticeae, Aveneae, Poeae, and Bromeae (Draper et al 2001;Kellogg 2001;Vogel et al 2006). Hence, the Brachypodium genome is expected to show greater gene colinearity to the genomes of major cool season cereal grain and forage grasses and will be more useful in gene discovery in large Triticeae genomes such as wheat and barley (Garvin et al 2008;Opanowicz et al 2008;Ozdemir et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…These changes can alter the functional relationships between orthologous genes in wheat and rice, making it difficult to predict the function in one species based on the function of the orthologue in the other species. Brachypodium is emerging as a better model system for wheat because of the more recent divergence of these two lineages (35-40 million years) compared to the wheat-rice divergence (Draper et al 2001;Hasterok et al 2006;Vogel et al 2006). Although the successful sequencing of Brachypodium will most likely be a valuable resource for wheat, the first comparative genomic studies are showing multiple alterations of colinearity between these two genomes (Bossolini et al 2007;Valarik et al 2007) suggesting that a final validation of gene function directly in wheat will still be necessary.…”
Section: Introductionmentioning
confidence: 99%